Effects of IL-6, JAK, TNF inhibitors, and CTLA4-Ig on knee symptoms in patients with rheumatoid arthritis - Koichi Murata; Ryuji Uozumi; Takayuki Fujii; Akira Onishi; Kosaku Murakami; Hideo Onizawa; Masao Tanaka; Akio Morinobu; Shuichi Matsuda (Scientific Reports)
Abstract This study aims to identify factors influencing the alleviation of knee joint symptoms in patients with rheumatoid arthritis treated with biologic or target synthetic disease-modifying antirheumatic drugs (b/tsDMARDs). Among 2321 patients who started b/tsDMARDs between 2010 and 2023, we focused on 295 patients who had knee swelling or tenderness at the initiation of b/tsDMARDs and continued b/tsDMARDs at least 3 months, with recorded knee symptoms 6 months later. Symptom relief after 6 months was 78.2% for interleukin 6 (IL-6) inhibitors, 68.6% for Janus kinase (JAK) inhibitors, 65.8% for tumor necrosis factor (TNF) inhibitors, and 57.6% for cytotoxic T lymphocyte-associated antigen-4-Ig (CTLA4-Ig). The initial use of b/tsDMARDs and the use of IL-6 inhibitors in comparison to CTLA4-Ig emerged as a significant factor associated with the improvement of knee joint symptoms. Among 141 patients who underwent knee radiography at baseline and two years later, the deterioration in knee joint radiographs was 7.7% for IL-6 inhibitors, 6.3% for JAK inhibitors, 21.9% for TNF inhibitors, and 25.9% for CTLA4-Ig. The use of IL-6 inhibitors was a significant factor associated with the improvement of knee joint symptoms and the inhibition of joint destruction compared to CTLA4-Ig.